(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Patient Safety Culture (PSC) is an essential component for service quality improvement. There have few studies on PSC conducted in district level hospitals in Vietnam. Objectives: This study aims to assess the current situation of PSC at Le Van Viet hospital, Ho Chi Minh City in 2022. Methods: We applied a cross-sectional design to perform self-administered interviews with all 192 health providers in Le Van Viet hospital. We used HSOPSC-VN2015 to evaluate the PSC of the hospital. Findings: The positive and negative rate of PSC was 59.6% and 11.8%. Out of the total 12 dimensions of PSC, four dimensions with highest positive rate (>70%) were Teamwork Within Units, Supervisor/ Manager Expectations & Actions Promoting Patient Safety, Organizational Learning-Continuous Improvement, and Feedback & Communication About Error. The three dimensions with lowest positive rate were Handoffs & Transitions (35.8%), Staffing (37.6%), and Nonpunitive Response to Errors (45.3%) Conclusion: The positive rate of PSC was 59.6% at Le Van Viet hospital. The study results recommend the need to strengthen human resource, improve equipment and facility and develop policy to support medical error report.